Faktor-Faktor Penentu Perilaku Hidup Bersih dan Sehat (PHBS) di Lingkungan Rumah Tangga di Kelurahan Tafraka - Hairuidin La Patilaiya; Hamidah Rahman; Amalan Tomia; Sirnilanti Udin; Aljufri Radjak (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Clean and Healthy Living Behavior (PHBS) plays an important role in improving public health at the household level, especially in areas with limited access to health services such as Tafraka Village, Pulau Hiri District, Ternate City. This study aims to describe the implementation of PHBS and identify factors associated with its practice. The study employed a descriptive analytical survey design with a quantitative approach. Data were collected using questionnaires administered to 118 heads of households. Data analysis was conducted bivariately using the chi-square test with a significance level of α = 0.05. The results showed that 89 respondents (75.4%) had implemented PHBS, while 29 respondents (24.6%) had not implemented it optimally. Variables such as gender, age, education, occupation, and knowledge were significantly associated with the implementation of PHBS (p < 0.05). Knowledge and sociodemographic factors contributed to variations in PHBS practices. These findings highlight the importance of health promotion efforts and continuous education tailored to community characteristics to improve the implementation of PHBS.